2022
DOI: 10.1542/peds.2021-052561
|View full text |Cite
|
Sign up to set email alerts
|

Maternity Care Practices and Breastfeeding Intentions at One Month Among Low-Income Women

Abstract: BACKGROUND: Maternity care practices have been linked with higher chances of meeting breastfeeding intentions, but this relationship has not been examined using national data on US low-income women enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). METHODS: Using data from the WIC Infant and Toddler Feeding Practices Study-2 on 1080 women who intended to breastfeed, we estimated ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The current study adds to a growing body of literature reporting that receiving more BF supports at the hospital is associated with increased likelihood and duration of BF. Previous research has established a dose-response relationship between BF-friendly hospital practices and BF initiation [ 17 ], EBF at the hospital [ 21 ] and 1 wk postpartum [ 16 ], and meeting intentions to fully BF at 1 mo [ 23 ]. However, studies examining the association between the number of hospital supports and later BF have yielded somewhat mixed results [ 20 , 21 , 41 ], which may be related to methodological differences and/or regional differences in BF culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study adds to a growing body of literature reporting that receiving more BF supports at the hospital is associated with increased likelihood and duration of BF. Previous research has established a dose-response relationship between BF-friendly hospital practices and BF initiation [ 17 ], EBF at the hospital [ 21 ] and 1 wk postpartum [ 16 ], and meeting intentions to fully BF at 1 mo [ 23 ]. However, studies examining the association between the number of hospital supports and later BF have yielded somewhat mixed results [ 20 , 21 , 41 ], which may be related to methodological differences and/or regional differences in BF culture.…”
Section: Discussionmentioning
confidence: 99%
“…The WIC Infant and Toddler Feeding Practices Study II (ITFPS-2), which aimed to update and expand data on feeding practices and behaviors among infants and toddlers being served by WIC, provides a nationally representative sample of English- or Spanish-speaking WIC participants. Data from ITFPS-2 have previously demonstrated that initiating BF within 1 h of birth, providing no foods or drinks other than breastmilk, not providing pacifiers, and experiencing more BFHI steps overall increased the likelihood of meeting BF intentions at 1 mo of age [ 23 ]. However, in that study, neither the influence of receiving a pro-formula gift pack nor BF outcomes beyond 1 mo were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding counseling during pregnancy has been linked to an increase in the likelihood of meeting breastfeeding intentions and practices during the postnatal period. Women who experienced supportive antenatal care practices were more likely to fulfill their prenatal breastfeeding intentions mainly initiation of breastfeeding within one hour and giving only breast milk in the first six months [19].…”
Section: Breastfeeding Support During Pregnancymentioning
confidence: 99%
“…The place of delivery was the integral component for the promotion and actual implementation of optimal breastfeeding practices. Effective breastfeeding support during labor and delivery hospitalization is crucial for mothers to be able to achieve their breastfeeding goals [19].…”
Section: Breastfeeding Support During Labor and Deliverymentioning
confidence: 99%
“…Timely breastfeeding initiation in Cambodia remains low. While breastmilk substitute promotion persists [ 17 ] and BFHI compliance assessment is lacking [ 28 , 29 ], health professionals and facilities can protect breastfeeding by promoting SSC, rooming-in, recruiting government support, and offering lactation counseling [ 30 , 31 ]. With two-thirds of public health professionals working privately in Cambodia [ 26 ], crossover training has greater potential across sectors for breastfeeding advocacy.…”
Section: Introductionmentioning
confidence: 99%